2020
DOI: 10.3390/su12104044
|View full text |Cite
|
Sign up to set email alerts
|

A New Comprehensive Approach for Efficient Road Vehicle Procurement Using Hybrid DANP-TOPSIS Method

Abstract: The efficient vehicle procurement is an important business segment of different companies with their own vehicle fleet. It has a significant influence on reducing transport and maintenance costs and on increasing the fleet’s energy efficiency. It is indispensable that managers consider various criteria from several aspects when procuring a vehicle. In that sense, we defined 13 relevant criteria and divided them into four multidisciplinary aspects: Construction-technical, financial, operational, and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Kim et al [25] used the DANP method to develop a three-stage complexity prioritization after investigating the reliability and feasibility options, and their case study validation results showed that consultant competency, uncertainty of scope, site compensation and permitting, stakeholder communication between parties, administrative procedures, and project deadlines are the most important criteria for the project. Marko et al [26] used the DANP methodology and employed 50 experts in the field, developing a new model to consider the procurement of company vehicles from four perspectives: construction technology, financial, operational, and environmental aspects. A total of 13 relevant criteria are defined in the vehicle, and the relevant weights are obtained.…”
Section: Danpmentioning
confidence: 99%
“…Kim et al [25] used the DANP method to develop a three-stage complexity prioritization after investigating the reliability and feasibility options, and their case study validation results showed that consultant competency, uncertainty of scope, site compensation and permitting, stakeholder communication between parties, administrative procedures, and project deadlines are the most important criteria for the project. Marko et al [26] used the DANP methodology and employed 50 experts in the field, developing a new model to consider the procurement of company vehicles from four perspectives: construction technology, financial, operational, and environmental aspects. A total of 13 relevant criteria are defined in the vehicle, and the relevant weights are obtained.…”
Section: Danpmentioning
confidence: 99%
“…It can determine the interdependence among the indicators and reduce the frequency of pairwise comparisons between elements when calculating the weights, thus reflecting the reality more objectively [12,13]. In recent years, the DANP method has been well applied in the research of online catering platform evaluation [14], vehicle procurement evaluation [15], electronic health record evaluation [16], and green building evaluation [17]. There are few studies on applying the DANP method to the OGDP evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Transportation and logistics companies with a vehicle fleet in goods road transportation have the aim to realize all planned transportation tasks in the observed time, simultaneously generating as low costs as possible so as to make a bigger profit. As fuel consumption for the realization of transportation tasks has a significant share in costs [1][2][3], an increase in the energy efficiency of a vehicle fleet is one of the significant measures for achieving the goal of the considered companies [4][5][6] and is yet increasingly gaining in importance when the environment is observed since road transportation has a dominant share in final energy consumption in the transportation sector [7][8][9].…”
Section: Introductionmentioning
confidence: 99%